Perception of discretionary accounting for business combinations. An ethical approach - Maruszewska, Ewa Wanda (Postrzeganie uznaniowych regulacji rachunkowości w obszarze połączeń jednostek. Perspektywa etyczna, 2020)
This paper investigated how Polish students of accounting perceive the lack of precision of accounting regulations for business combinations. It was hypothesized and confirmed that young accountants show the propensity to exercise discretion in the accounting for business combinations to the detriment of faithfulness of financial information. The study is based on a survey questionnaire of 91 accounting faculty students. The responses suggest that the unethical usage of flexibility in accounting is justified by many situational factors. Although it is difficult to generalize the results, the findings are useful in demonstrating how ethical enhancement is needed in both education and accounting regulations
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 8, s. 83-92